Recurrent Vocal Fold Paralysis and Parsonage-Turner Syndrome - Marcus Vinicius Pinto; Lucia Joffily; Maurice Borges Vincent (Case Reports in Otolaryngology)
Background. Parsonage-Turner syndrome, or neuralgic amyotrophy (NA), is an acute brachial plexus neuritis that typically presents with unilateral shoulder pain and amyotrophy but also can affect other peripheral nerves, including the recurrent laryngeal nerve. Idiopathic vocal fold paralysis (VFP) represents approximately 12% of the VFP cases and recurrence is extremely rare. Methods and Results. We report a man with isolated recurrent unilateral right VFP and a diagnosis of NA years before. Conclusions. We emphasize that shoulder pain and amyotrophy should be inquired in any patient suffering from inexplicable dysphonia, and Parsonage-Turner syndrome should be considered in the differential diagnosis of idiopathic VFP.